COMBINED METHOD OF SHOOTING PLAN OF THE RAILWAY LINE - Korzhenievych, I. P. (Science and Transport Progress, 2007)
The combination of existing methods of surveying curves has been considered and recommendations on leveling-off the results of measurements have been given.